STUDY ANALYSIS IN THE TERMINAL FACILITIES PEDESTRIANS JOYOBOYO SURABAYA - Diky Efendi; Atik Wahyuni (NAROTAMA UNIVERSITY, Indonesia, 2020)
Pedestrian is a term that describes the transport of people walking in a special place pedestrian. Surabaya is a metropolitan city and one of the cities that serve the community for a vacation like to Surabaya Zoo (KBS) is located not far from the terminal Joyoboyo. The present study was to determine the characteristics of the pedestrian (flow, speed, density), determine the condition of the geometry of pedestrian facilities, pedestrian facilities as well as performance analysis method used is the ratio. This research method includes several stages of site survey, then the data collection that uses several pedestrian walkways, noting the results of a survey conducted during the second day on Sunday and Tuesday at 06:00 to 09:00, measurement speed, geometry condition surveys and questionnaires about the identity, purpose and the purpose, time and distance pedestrian. The analysis showed that the dominant Pedestrian use the sidewalk at 8:45 a.m. to 9:00, the variable max on Sunday ie max speed of 64.78 m / min, max density pedestrian 43.47 /, While the variable-ratio 0.03 max on Tuesday that max speed 61.15 m / min, max density 37.51 pedestrian/, Max ratio of 0.032. While the performance of pedestrian facilities in the category